Pengembangan Metode PBL Menggunakan Media Interaktif Berbasis Web (Canva) Untuk Siswa Kelas XII RPL SMKN 2 Padang - Anaperta, Megasyani; Sari, Putri Yunita; Wingsky, Monica; Sari, Umi Kurnia; Zalukhu, Yasona (Journal of Computer Science and Information System(JCoInS), 2023)
Based on the results of interviews and observations of Database learning at SMKN 2 Padang, it shows that the learning process is good and teachers teach according to the curriculum. The media used are textbooks and presentation media using Power Point. Package books are used when the class does not have time to borrow infocus due to the limited number of infocus and not all students have laptops and there are problems with the computer laboratory being inadequate or unusable. The power point presentation media used is still monotonous or does not use interactive media, even though internet services such as Wifi are already available at schools. This research aims to produce interactive, valid, practical and effective media to use in helping students learn the hierarchical structure of databases. Learning media is created using Web-based Canva so that it can be used using each smartphone. The method used is R&D (Research and Development) with a 4D development model (Define, Design, Development and Deseminate) and using the Problem Based Learning Method. The research results show that this interactive learning media is said to be valid by validators and is considered practical by teachers and students based on the results of questionnaire responses. This shows that Web-based interactive learning media is declared effective in the learning process to improve the quality of student learning.